Comparative study of sintered and composite brake pad for wind turbine applications. (July 2023) - Sai Balaji, M.A.; Katiyar, Jitendra Kumar; Eakambaram, A.; Baskara Sethupathi, P.; Kamalakannan, J.; Baskar, A.
The sintered brake pads have been the most commonly utilized brake pads in wind turbines, as it stalls the rotor after shutdown or in case of emergencies. It is a mixture of metallic particles that are pressed together. But it has been noticed that the friction at interface generates the spark in adverse conditions, which cause a fire in nacelle. Due to this a compact unit for fire suppression is used, which adds the additional cost in brake system. Therefore, it is necessary to address the spark issues coming from brake pads under adverse conditions through developing a brake pad using alternate route. Hence, a composite brake button was developed through a compression moulding route, that is, cost economic route. Despite the different compositions and manufacturing routes of materials, a similar frictional behaviour is observed after testing using friction test rig. Further, it is observed a marginally higher friction values for sintered pads. Moreover, the physical and mechanical properties like density, hardness, porosity, shear strength, compression strength, etc., are also found to be similar. In fact, the density of a composite pad is observed 34.7% lesser than sintered pad. Both the developed brake pads have a mean dynamic friction coefficient (∼0.4–0.5) with a mean static friction coefficient of approximately 0.45. In spite of more hardness, the wear resistance is found poorer in sintered pads as compared with composite pads. Hence, it can be concluded that the developed composite pad shows better tribomechanical performance and suitable for application without spark issues.